2018
DOI: 10.1111/jcmm.13960
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA let‐7a regulates angiogenesis by targeting TGFBR3 mRNA

Abstract: Angiogenesis has a great impact on human health, owing to its participation in development, wound healing and the pathogenesis of several diseases. It has been reported that let‐7a is a tumour suppressor, but whether it plays a role in angiogenesis is unclear. Here we showed that let‐7a, a microRNA conserved in vertebrates, regulated angiogenesis by concomitantly down‐regulating TGFBR3. Overexpression of let‐7a or knockdown of TGFBR3 in cell culture inhibited the tube formation and reduced migration rate. More… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0
1

Year Published

2019
2019
2025
2025

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 57 publications
0
22
0
1
Order By: Relevance
“…Let-7a plays a prominent role in cell growth and differentiation [60], which may contribute to cerebrovascular endothelial function. In addition, overexpression of let-7a regulates angiogenesis by targeting TGFBR3 and reduces endothelial cell migration rate, in vitro [61]. Other studies from our laboratory have noted BBB leakage Fig.…”
Section: Discussionmentioning
confidence: 73%
“…Let-7a plays a prominent role in cell growth and differentiation [60], which may contribute to cerebrovascular endothelial function. In addition, overexpression of let-7a regulates angiogenesis by targeting TGFBR3 and reduces endothelial cell migration rate, in vitro [61]. Other studies from our laboratory have noted BBB leakage Fig.…”
Section: Discussionmentioning
confidence: 73%
“…Altered miR-146a-5p/miR-132-3p and Let-7a-5p/miR-16-5p are the most relevant ratios to identify patients with vasomotor deficits from those without these deficits and controls. Concordantly, alterations in all these miRNAs have been described in angiogenesis-related diseases [ 110 , 111 , 112 ]. Our data point to increased circulating miR-146a-5p/miR-132-3p ratio as a hallmark of RTT that can identify patients from controls with very good accuracy, while it also serves to stratify RTT severity, being able to discriminate those patients with microcephaly or vasomotor deficits.…”
Section: Discussionmentioning
confidence: 90%
“…Let-7a inhibits tube formation and reduces the migration rate of HUVECs by directly targeting transforming growth factor beta (TGFβ) receptor III, resulting in a defective TGFβ signaling pathway in these cells [87]. Sureban et al demonstrated that, in pancreatic cancer and HCC, doublecortin-like kinase 1 (DCLK1), a putative marker of intestinal and pancreatic stem cells, regulates the pluripotency and expression of angiogenic factors via miRNA-dependent mechanisms.…”
Section: Let-7amentioning
confidence: 99%